Perceptions of Novice and Experienced Translators toward the Role of High-quality Translated Tourism Promotional Materials (TPMs) in Promoting the Tourism Industry in Saudi Arabia - Ali Albashir Mohammed Alhaj (Taez University, 2024)
In today's world, high-quality translated tourism promotional materials (TPMs) play a leading role in developing business sectors in general and the tourism sector in particular because TPMs are the most often used forms of media targeting actual tourists and other audiences. This study explored the perceptions of novice and experienced translators about the role of high-quality translated TPMs in promoting the tourism industry in Saudi Arabia. Fifty novice and experienced translators in Saudi Arabia participated in this study. Data gathering comprised quantitative data. The findings of the study revealed that a lot of participants (57.00%) had positive perceptions toward the role played by high-quality translated TPMs in promoting the tourism industry in Saudi Arabia. The findings also demonstrated that many of the respondents (60.85%) perceive that the main challenge in the translation of TPMs is culture-specific items that may be comparatively prevalent to the native population but unfamiliar to people outside that certain community.